2021
DOI: 10.1016/j.chest.2020.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Paired Nasopharyngeal and Deep Lung Testing for Severe Acute Respiratory Syndrome Coronavirus-2 Reveals a Viral Gradient in Critically Ill Patients

Abstract: Since the start of the coronavirus 2019 (COVID-19) pandemic, arising from Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) viral infection, approximately 13,000 patients have been admitted to critical care in the United Kingdom; most have required advanced respiratory support. 1 Samples for SARS-CoV-2 detection can be obtained from the upper (nasopharyngeal/oropharyngeal swabs) or lower respiratory tract (sputum/endotracheal aspirate/BAL). 2 Viral RNA is detected using reverse transcriptase polymer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…These include a later stage of disease during which viral replication is less pronounced 24 , higher viral loads in the lower rather than upper respiratory tract in critically ill patients 25 and use of respiratory devices, which reduce aerosol generation 20 . The reduction in microbial bioaerosols found in ICU during the week of the air filtration system provides confidence that the device was similarly effective to that used on the ward, despite the infrequent detection of SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 99%
“…These include a later stage of disease during which viral replication is less pronounced 24 , higher viral loads in the lower rather than upper respiratory tract in critically ill patients 25 and use of respiratory devices, which reduce aerosol generation 20 . The reduction in microbial bioaerosols found in ICU during the week of the air filtration system provides confidence that the device was similarly effective to that used on the ward, despite the infrequent detection of SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 99%
“…[11]. However, ACE2 receptors are also found throughout the respiratory tree including on the alveolar epithelial cells, and therefore inhalation of smaller infectious aerosol particles <5 µm that can travel deeper into the lungs may also contribute to the burden of disease [12, 13].…”
Section: Introductionmentioning
confidence: 99%
“…Severe COVID-19 patients with a high dosage of CQ treatment even had a high rate of fatality, resulting in the early termination of the relevant studies [ 25 ]. SARS-COV-2 PCR tests showed that most severe COVID-19 patients had higher positive rates for samples from deep lung [ 30 ]. Recently, CQ and HCQ have been found to be unable to block the SARS-COV-2 infection in human lung cells [ 26 ], showing that CQ and HCQ have no ability to prevent SARS-CoV-2 from affecting the lungs of severe COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%